2012
DOI: 10.1111/j.1399-0012.2012.01691.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study on living related kidney donors’ quality of life in the first year: choosing appropriate reference data

Abstract: Prospective studies on living kidney donors' quality of life (QoL) are still rare. Most existing studies compare healthy donors with the general population, including subjects with diseases. This is the first prospective study comparing living donors' QoL with reference data of both the general population and healthy individuals. We investigated QoL, anxiety, and depression in living kidney donors (n = 79) before donation and at two post-operative data points (three months and one yr). Subsequently, data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
45
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 38 publications
2
45
1
2
Order By: Relevance
“…Perception of their recipients’ current health status as being low also characterized LKDs that where somewhat dissatisfied. Contrary to our expectations, and previous studies , differences between clusters were statistically significant but such low that seemed to be clinically non‐relevant. To further assess the relevance, its ability to differentiate between clusters was analyzed by ROC curve which showed that donor perception of their recipient's health was unable to differentiate between groups (data not shown).…”
Section: Discussioncontrasting
confidence: 99%
“…Perception of their recipients’ current health status as being low also characterized LKDs that where somewhat dissatisfied. Contrary to our expectations, and previous studies , differences between clusters were statistically significant but such low that seemed to be clinically non‐relevant. To further assess the relevance, its ability to differentiate between clusters was analyzed by ROC curve which showed that donor perception of their recipient's health was unable to differentiate between groups (data not shown).…”
Section: Discussioncontrasting
confidence: 99%
“… found an association between unfavorable recipient outcomes and a lower quality of life among donors. Two other studies similarly found that donors who perceived the health status of their recipients as worse had more psychological problems than other donors .…”
Section: Introductionmentioning
confidence: 82%
“…12,[14][15][16][17][18][19][20][21][22][23][24][25][26][27] The studies published to date suffer from design limitations and are either retrospective, [14][15][16][17][18][19][20][21][22][23][30][31][32][33][34][35] from a single center, 12,[14][15][16][17][18][24][25][26][28][29][30] or involve fewer than 150 donors. 12,[14][15][16][21][22][23][24][25]…”
Section: Introductionmentioning
confidence: 99%